On the use of technique and technology in education (2019)
This text reflects upon the impact of Information and Communication Technologies (ICT) on education from a philosophical, historical and hermeneutical point of view. The results show that, currently, there is a problem of comprehension of the concepts of educational technique and technology, evidenced in the different ways of interpreting and evaluating the appearance of ICT in education. In the end, it is proposed to continue the debate on technique and technology in the various teaching and learning processes.